The Entrepreneurship-Philanthropy Nexus: Implication for Internationalization - Zoltán J. Ács; Pontus Braunerhjelm (Max Planck Institute for Research into Economic Systems, 2004)
This paper examines how Sweden and the United States have been impacted by philanthropic activities, commercialization of university-based knowledge and international entrepreneurship. The analysis comprises a detailed case study of Swedish and U.S. universities, as well as a statistical analysis of the impact of philanthropy on economic growth. The results show that the United States has prompted a university system based on competition and variety, with an emphasis on philanthropy, promoting knowledge creation. International entrepreneurship has been an important mechanism by which this knowledge is globalized leading to increased economic growth. Conversely, Swedish universities were characterized by less commercialized R&D and weak links to the commercial sector, rooted traditionally in dependence on tax -financed and homogenous university structure. The Swedish model has begun to change with important implications for development in smaller domestic markets. The analysis has important implications for knowledge creation as a source of economic growth through international entrepreneurship taking advantage of globalization, especially for smaller countries.
Keywords: 330; Unternehmer; Multinationales Unternehmen; Hochschulfinanzierung; Sponsoring; Wohltätigkeit; Forschungskooperation; Wirtschaftswachstum